PERAN PUSAT LAYANAN INFORMASI PUBLIK STUDI PADA MEDIA CENTER PROVINSI KALIMANTAN SELATAN - ade nur atika sari; Risa Dwi Ayuni; Sitna Hajar Malawat; Lieta Dwi Novianti (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2022)
Media Center is a means of mass communication run by the government as a provider of public information. News about government work programs that are being implemented and policies taken can be monitored continuously by the community. Freedom and ease of access to information will help minimize communication crises in the form of suspicion and sensational information circulating in the community. Media Center becomes very influential for the community if the information provided is comprehensive and always contains news updates. This study aims to determine the role of the Media Center of South Kalimantan Province as a provider of public information. The method used is a qualitative approach by choosing the type of descriptive case study research. The output target is the publication of a national journal.